Copper fumarate with high-bifunctional nanozyme activities at different pH values for glucose and epinephrine colorimetric detection in human serum. Issue 1 (24th November 2021) - Ying, Meihui; Yang, Guizeng; Xu, Yuanjie; Ye, Huiling; Lin, Xing; Lu, Yi; Pan, Haibo; Bai, Yang; Du, Min
Abstract : A colorimetric sensor based on Cu MOFs with fumaric acid as the ligand shows bifunctional enzyme activities, namely laccase activity at pH = 8 and peroxidase activity at pH = 4. Abstract : Metal–organic frameworks (MOFs) have attracted extensive attention for the development of colorimetric detection methods due to their ease of modification and high density of active sites. However, most of the reported colorimetric sensors based on MOFs show only a single nanozyme activity. Herein, the bifunctional enzyme activities of a hexagonal prism Cu MOF with fumaric acid as the ligand (Cu FMA), namely laccase-like activity under alkaline conditions (pH = 8) and peroxidase-like activity under acidic conditions (pH = 4), were verified. The specificity of Cu FMA at different pH values may be due to the presence of the Cu + active center introduced by the weak reducibility of FMA. At pH = 8, Cu + active centers are beneficial for dissociating the H–O bonds of phenolic compounds for the laccase system. In contrast, the dissociation of H–O is weakened at pH = 4, which prompts the breaking of the O–O bonds of H2 O2 as a Fenton-like reaction for the peroxidase system. Based on the dual enzyme activities, Cu FMA sensors exhibit outstanding detectability for epinephrine and glucose with linear ranges of 2.7–54.6 μM and 0.01–0.8 mM and detection limits of 1.1 μM and 2.28 × 10 −7 M, respectively. The Cu FMA colorimetric sensor can be applied for detecting and measuring glucose and epinephrine in human serum samples. This work paves the way for Cu MOFs to be used as the basis for rational regulation of the activity of dual nanozymes and for multifunctional applications under completely independent conditions.